2021
DOI: 10.3390/pathogens10091179
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Transcriptomic and Histologic Profiling Reveals Tissue Repair Mechanisms Underlying Resistance to the Parasite Ceratonova shasta

Abstract: Background: Myxozoan parasites infect fish worldwide causing significant disease or death in many economically important fish species, including rainbow trout and steelhead trout (Oncorhynchus mykiss). The myxozoan Ceratonova shasta is a parasite of salmon and trout that causes ceratomyxosis, a disease characterized by severe inflammation in the intestine resulting in hemorrhaging and necrosis. Populations of O. mykiss that are genetically fixed for resistance or susceptibility to ceratomyxosis exist naturally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 72 publications
(95 reference statements)
0
13
0
Order By: Relevance
“…7). GATA3 was previously found to be down-regulated in fish spleen and HK following exposure to myxozoan parasites E. leei and T. bryosalmonae [91,95]; however, in other reports it was up-regulated [25,51,88,96].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…7). GATA3 was previously found to be down-regulated in fish spleen and HK following exposure to myxozoan parasites E. leei and T. bryosalmonae [91,95]; however, in other reports it was up-regulated [25,51,88,96].…”
Section: Discussionmentioning
confidence: 84%
“…In fish, non-specific cytotoxic cell activity in HK was higher following infection by the myxozoan Enteromyxum leei [26]. Nonetheless, while some studies support this result and show higher expression of perforin, granzyme, or NK-lysin in fish infected by E. leei [91], Ceratonova shasta [25,52] or Myxobolus honghuensis [88], other works in fish infected by E. scophthalmi [54] or C. shasta [52] report down-regulation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Collagens, constituting of different types that can be subdivided into fibril-forming collagens, network-forming collagens, fibril-associated collagen with interrupted triple helices (FACIT), transmembrane collagens and finally multiplexins. A recent study for steelhead trout ( Oncorhynchus mykiss ) reported that the resistant fish have a different response to parasite infection at the tissue level with the collagenous stratum compactum acting as a barrier preventing parasite spreading ( 32 ). We found that the network-forming collagens (type IV collagen) col4a4 and col4a5 , which are the major nonfibril structural component of basement membranes, were up-expressed in skin tissue of the resistant families; The fibril-associated collagens with interruptions in their triple helices (FACITs), such as col6a2 , col6a3, col12a1 and col28a1 showed down-expressions in skin tissue; All the fibril-forming collagens (e.g., types I, II, III collagen) levels were not different ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…After passing mucosal and epithelial barriers, the parasite travels through the bloodstream to its specific target tissue, where it proliferates. Some myxozoans are terminated in the blood by cellular and humoral immune factors [ 23 , 24 , 25 ]. Once the parasite is at the target tissue, the host activates immune mechanisms including immunoactivating and immunosuppressive cytokines [ 17 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%